2012
DOI: 10.1016/j.ejmech.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and molecular hybrids of caudatin and cinnamic acids as novel anti-hepatitis B virus agents

Abstract: Forty-six conjugated derivatives of caudatin with substituted cinnamic acids were synthesized, and their anti-hepatitis B virus (HBV) activity was evaluated in HepG 2.2.15 cells. Most of the derivatives exhibited potent anti-HBV activity, especially inhibiting the HBV DNA replication with the IC(50) values from 2.44 to 22.89 μΜ. Compound 18 showed significant activity against the secretion of HBsAg, HBeAg, and HBV DNA replication with IC(50) values of 5.52, 5.52, 2.44 μΜ, respectively, and had good safety (LD(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In our previous studies, caudatin induced apoptosis of AGS cells or the HGC-27 cell line (14). Wang et al found that caudatin had an inhibitory activity on the secretion of HBsAg and HBV DNA replication (17). Furthermore, caudatin as a prospective anti-HCC drug with the mechanism of inhibiting cell proliferation and inducing cell apoptosis has been reported (18).…”
Section: Introductionmentioning
confidence: 91%
“…In our previous studies, caudatin induced apoptosis of AGS cells or the HGC-27 cell line (14). Wang et al found that caudatin had an inhibitory activity on the secretion of HBsAg and HBV DNA replication (17). Furthermore, caudatin as a prospective anti-HCC drug with the mechanism of inhibiting cell proliferation and inducing cell apoptosis has been reported (18).…”
Section: Introductionmentioning
confidence: 91%
“…The [M−H] − ions for metaplexigenin (1), caudatin (2), qingyangshengenin (3), and penupogenin (4) were easily obtained. In contrast, only [M+H] + ions for 20-cinnamoylsarcostin (5) and gagamine (6) were observed. Therefore, the MS n investigations for steroids 1-4 in negative mode and for steroids 5-6 in positive mode were chosen, as shown in Tables 1-6.…”
mentioning
confidence: 98%
“…Recent studies demonstrated that caudatin induced the apoptosis of HepG2 cells or the SMMC772 cell line (6,7). Wang et al (8) found that caudatin had an inhibitory activity on the secretion of HBsAg and HBV DNA replication. Furthermore, caudatin as a prospective anti-HCC drug with the mechanism of inhibiting cell proliferation and inducing cell apoptosis has been reported (9).…”
mentioning
confidence: 99%